Development of Web-Based Islamic Religious Education Evaluation Instruments at The 1st State of SMP N 1 Laut Tador - Aulia Rahmah Puteri Rahmah; Salminawati Salminawati; Zaini Dahlan (JURNAL ASIMILASI PENDIDIKAN, 2026)
This study aims to: (1) develop a web-based Islamic Religious Education (PAI) learning evaluation instrument at the UPT SMP Negeri 1 Laut Tador using the ADDIE development model; (2) determine the instrument's validity based on expert assessments; (3) determine the instrument's practicality based on teacher and student responses; and (4) determine the instrument's effectiveness in improving the quality of PAI learning evaluation. This research is a Research and Development (R&D) study using the ADDIE model, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. The research subjects consisted of material experts, media experts, evaluation experts, PAI teachers, and students at UPT SMP Negeri 1 Laut Tador. Data collection techniques used expert validation sheets, teacher and student response questionnaires, and learning outcome tests. Data were analyzed descriptively and quantitatively using a percentage formula to determine the product's feasibility category. The results indicate that the developed web-based PAI evaluation instrument is categorized as highly valid based on assessments by material experts, media experts, and evaluation experts. Teacher and student responses indicate a highly practical category, making the instrument easy to use in the learning evaluation process. Furthermore, the effectiveness test results demonstrated that the use of web-based instruments increased student engagement and provided more objective, faster, and more efficient evaluation results compared to conventional evaluations. Thus, the developed web-based Islamic Religious Education evaluation instrument was deemed feasible, practical, and effective for use in supporting the Islamic Religious Education learning evaluation process at the UPT SMP Negeri 1 Laut Tador.